PENINGKATAN PENDAPATAN PENGRAJIN TEDUNG DENGAN TEKNIK PEMASARAN E-COMMERCEDAN PENYUSUNAN LAPORAN KEUANGAN MENGGUNAKAN KOMPUTER DI DESA MEKAR BHUWANA KECAMATANABIANSEMAL KABUPATEN BADUNG - Rai Dwi Andayani W (JURNAL SEWAKA BHAKTI, 2020)
Mekar Bhuwana Village, Abiansemal Subdistrict, Badung Regency, where some residents in terms of livelihoods work as building craftsmen to meet family needs. In carrying out their business, the building craftsmen have not applied modern marketing techniques, the way to market their products is done by depositing their products in small shops that sell religious tools according to orders and in preparing their financial statements they have not used technology such as computers to run this business. so it is not yet known how much the production costs, profits and losses were experienced. Marketing techniques have a very important role in running a business because customer satisfaction is the final goal in marketing techniques, it is necessary to understand and understand proper marketing management. Financial reporting in a business is the final process of the accounting process. Based on this problem, we provide assistance and training on online marketing techniques and simple financial report preparation training so that this business can be more advanced and able to compete in all foreign markets. With this community service, it is hoped that the Building Craftsmen will be able to carry out online marketing techniques properly and be able to financial reports using computers.